Tropical Legumes: Resources for the Future - National Research Council (U.S.). (Washington: National Academy of Sciences, 1979)
This report describes plants of the family Leguminosae, all of them greatly underexploited. Some are extensively used in one part of the world but unknown elsewhere; others are virtually unknown to science but have particular attributes that suggest they could become major crops in the future; a few are already widespread but their possibilities are not yet fully realized.
Report of an ad hoc panel of the Advisory Committee on Technology Innovation, Board on Science and Technology for International Development, Commission on International Relations, National Research Council.
Includes bibliographies and index.
ne 5/04/2018
Loans
Keywords: Legumes; Tropical Crops